2022
DOI: 10.32604/ee.2022.019051
|View full text |Cite
|
Sign up to set email alerts
|

Latent Heat Prediction of Nano Enhanced Phase Change Material by ANN Method

Abstract: Thermal characteristics of phase change material (PCM) are important in design and utilization of thermal energy storage or other applications. PCMs have great latent heat but suffer from low thermal conductivity. Then, in recent years, nano particles have been added to PCM to improve their thermophysical properties such as thermal conductivity. Effect of this nano particles on thermophysical properties of PCM has been a question and many experimental and numerical studies have been done to investigate them. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 64 publications
(69 reference statements)
0
0
0
Order By: Relevance
“…It was reported that the trained neural network was sufficient to predict the experimental data, achieving a coefficient of determination (R 2 ) of 0.9985 and 0.9973 during the sampling of the training and testing datasets, respectively. Jaliliantabar et al [25] collected a dataset comprising twenty different nanoparticles to develop an AI-based model for the prediction of latent heat of an NEPCM. The training input layer consisted of nine neurons including a density of dispersed nanoparticles, particle size, latent heat value of PCM, density of pure PCM, and latent heat of the NEPCM.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the trained neural network was sufficient to predict the experimental data, achieving a coefficient of determination (R 2 ) of 0.9985 and 0.9973 during the sampling of the training and testing datasets, respectively. Jaliliantabar et al [25] collected a dataset comprising twenty different nanoparticles to develop an AI-based model for the prediction of latent heat of an NEPCM. The training input layer consisted of nine neurons including a density of dispersed nanoparticles, particle size, latent heat value of PCM, density of pure PCM, and latent heat of the NEPCM.…”
Section: Introductionmentioning
confidence: 99%